2008
DOI: 10.1074/mcp.m800069-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CKAP4/p63 as a Major Substrate of the Palmitoyl Acyltransferase DHHC2, a Putative Tumor Suppressor, Using a Novel Proteomics Method

Abstract: The recent discovery of at least 23 enzymes that mediate palmitoylation (palmitoyl acyltransferases or PATs 1 ) suggests that regulation of palmitoylation is far more complex than previously assumed. Defining PAT-substrate specificities in living vertebrate systems is a critical next step in understanding the complexity of regulated palmitoylation and the potential consequences of malfunctioning PATs on downstream signaling events. To date, five PAT genes have been implicated in human diseases ranging from sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
129
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(138 citation statements)
references
References 48 publications
9
129
0
Order By: Relevance
“…Similar to the results seen for phosphorylation, the blocking of palmitoylation decreases CKAP4 binding to microtubules [22]. A group of at least 23 enzymes called palmitoyl acyltransferases (PATs), which are characterized by an Asp-His-His-Cys (DHHC) motif, have been determined to mediate palmitoylation [23].…”
Section: Ckap4 Structurementioning
confidence: 64%
“…Similar to the results seen for phosphorylation, the blocking of palmitoylation decreases CKAP4 binding to microtubules [22]. A group of at least 23 enzymes called palmitoyl acyltransferases (PATs), which are characterized by an Asp-His-His-Cys (DHHC) motif, have been determined to mediate palmitoylation [23].…”
Section: Ckap4 Structurementioning
confidence: 64%
“…10 Previous reports suggested that CKAP4 palmitoylation by DHHC2 is required for its trafficking from the endoplasmic reticulum to the plasma membrane and for its nuclear localization, which is critical to the antiproliferation effect of CKAP4. 19 It is therefore of interest to investigate the expression and clinical significance of DHHC2 in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that palmitoylation by DHHC2, a putative tumor suppressor, is required for CKAP4 trafficking from the endoplasmic reticulum to the plasma membrane and for its nuclear localization. 10 Additional studies have reported that CKAP4 contributes to gentamicin-induced apoptosis in proximal tubule cells, likely through dimerization of CKAP4, which is dependent on its palmitoylation. 11 In the current study, we examined the pattern of expression of CKAP4 and DHHC2 in HCC tumor tissues and normal-like specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Using a technique called palmitoyl-cysteine isolation capture and analysis, she identified substrates of ZDHHC2 in HeLa cells, including CKAP4/p63, a receptor for antiproliferative factor (APF). APF is increased in patients suffering from interstitial cystitis [5]. Following up on this finding, she demonstrated that knock-down of ZDHHC2 inhibited the anti-proliferative activity of APF in cancerous and normal epithelium.…”
Section: Introductionmentioning
confidence: 82%